The Impact of Fulvic Acids on Cotton Growth, Yield and Phosphorus Fertilizer Use Efficiency Under Different Phosphorus Fertilization Rates in Xinjiang, China - Kai Zhang; Xiaopeng Gao; Chao Ma; Bing Chen; Fang Yuan; Jiandong Sheng (Agronomy)
Chemical phosphorus (P) fertilizer is often overused in arid regions with alkaline soils due to soil fixation. Fulvic acid (FA) can increase soil P availability, enhancing crop yield and P use efficiency, but its interaction with P fertilization rates and potential to reduce P fertilizer application remains unclear. A 2-year (2019–2020) field experiment was conducted in Xinjiang, China, to study the impact of FA addition (45 kg ha−1) on cotton yield and P use efficiency under different P fertilization rates (0, 50, 100 and 150 kg P2O5 ha−1). Our results showed that P fertilization significantly enhanced cotton biomass, P uptake and seed cotton yields by 17–37%, but the partial nutrient balance (PNB), agronomic efficiency (AE) and partial factor productivity (PFP) decreased with increasing P fertilization rates. FA addition did not change cotton biomass and P uptake, but significantly enhanced seed cotton yield, AE and PFP by increasing bolls per plant. No significant interactions between FA addition and P fertilization rates were observed for cotton biomass, P uptake, seed cotton yield and P use efficiencies. These findings suggest that FA can improve cotton productivity, AE and PPF of P fertilizers, helping to keep the P balance in the cotton field.